THE RECALIBRATION OF CHINA’S GRAND STRATEGY DURING THE BIDEN ADMINISTRATION - Mitić, Aleksandar; Stekić, Nenad (Serbian political thought, 2025)
Amid the continuous rise of China’s diplomatic, technological, military, economic and normative power, in the context of the transition to multipolarity, Washington has expanded its competition and rivalry with Beijing under the Joseph Biden administration. In addition to Donald Trump’s “tariff wars”, Biden’s presidency presented elements of a “containment 2.0” policy, upgraded with a strong liberal internationalist discourse on the need to uphold the “rules-based world order” (RBO) and a Manichean “democracy vs. autocracy” narrative. It led to the boosting of the RBO narrative against “authoritarian states”, the building of alliances against the Russian Federation and China, and new formats of securitization of globalization and weaponization of the global value chain. Beijing thus faced the Biden administration in a complex geopolitical environment and had to adapt its grand strategy. In response to the RBO, China proposed “true multilateralism”. Faced with a host of new “mini-alliances” in the Asia-Pacific, China boosted its military prowess. Beyond the region, Beijing pursued the expansion of existing (Belt and Road Initiative, Shanghai Cooperation Organization, BRICS) and new multilateral initiatives (Global Development Initiative, Global Security Initiative, Global Development Initiative). China demonstrated resilience and strategic foresight, while the agility and coherence of its evolving grand strategy have allowed Beijing to “welcome back” Donald Trump into the White House with readiness and self-confidence despite a “rocky road ahead”.